2007
DOI: 10.1016/j.heares.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone morphogenetic protein 4 in inner ear development and function

Abstract: Bone Morphogenetic Protein 4 (BMP4) is a member of the TGF-β superfamily and is known to be important for the normal development of many tissues and organs, including the inner ear. Bmp4 homozygous null mice die as embryos, but Bmp4 heterozygous null (Bmp4 +/− ) mice are viable and some adults exhibit a circling phenotype, suggestive of an inner ear defect. To understand the role of BMP4 in inner ear development and function, we have begun to study C57BL/6 Bmp4 +/− mice. Quantitative testing of the vestibulo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Notably, our Bmp4 Tm1/+ mice in Black Swiss background do not circle but a small percentage of Bmp4 heterozygous mice in C57BL/6 background do [35].…”
Section: Resultsmentioning
confidence: 81%
“…Notably, our Bmp4 Tm1/+ mice in Black Swiss background do not circle but a small percentage of Bmp4 heterozygous mice in C57BL/6 background do [35].…”
Section: Resultsmentioning
confidence: 81%
“…Bone Morphogenetic Protein 4 ( BMP4 ) is a member of the TGF-β superfamily and is known to be important for the normal development of many tissues and organs, including the inner ear. Recent studies have demonstrated that Bmp4 heterozygous null ( Bmp4+/− ) mice are viable and some adults exhibit an inner ear defect 37. Regarding VDR ( Vitamin D receptor ), it seems to be important for a wide range of reasons and it has several important biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…ABR measurements have proven to be a robust method for analyzing the effects of genetic mutations on hearing in mice, both in mutagenesis screens (Kermany et al, 2006) and in the evaluation of candidate genes (Abraira et al, 2007;Blauwkamp et al, 2007;Polley et al, 2006). In these studies, the candidate genes are transcription factors or morphogens with identified roles in nervous system development.…”
Section: Discussionmentioning
confidence: 99%